{Fertility potential in 5$α$-reductase type 2 deficient males.} - Markouli, Mariam; Michala, Lina (Journal of pediatric urology, 2023)
BACKGROUND: Males with 5$α$-reductase deficiency experience oligospermia or azoospermia, resulting in fertility problems. OBJECTIVE: The aim of the present systemic review was to assess the fertility status of males with 5$α$-reductase type 2 deficiency and explore how reproduction can be achieved in these patients. STUDY DESIGN: An extensive search of two databases (Pubmed and SCOPUS) was performed. Studies with original clinical data in patients with 5$α$-reductase deficiency evaluating the impact of the disease on semen quality and quantity and pregnancy outcomes through assisted or natural conception methods were eligible to be included in this systematic review. RESULTS: A total of nine cases were identified based on the eligibility criteria, all of which included reports of successful reproduction in males with 5$α$-reductase type 2 deficiency. DISCUSSION: In five individuals, assisted reproduction technology was used to achieve conception, highlighting its importance in solving the fertility problems that males with 5$α$-reductase deficiency are facing. Potential future fertility is a further indication for assigning the male gender in diagnosed newborns. CONCLUSION: In order to achieve this, the development of a management plan starting at birth is crucial for these patients, so that spermatogenesis and potential fertility can be preserved. In adulthood, semen analysis and mutation screening may also help in guiding these patients to select the correct fertilization method for their individual genetic and phenotypic characteristics.
Keywords: Cholestenone 5 alpha-Reductase; Female; Fertility; Humans; Infant; Male; Newborn; Oxidoreductases; Pregnancy; Semen Analysis